1982
DOI: 10.1128/iai.37.2.568-578.1982
|View full text |Cite
|
Sign up to set email alerts
|

Serum Regulation of In Vitro Lymphocyte Responses in Early Experimental Syphilis

Abstract: Sera from rabbits with early experimental syphilis were tested for their effect on in vitro lymphocyte transformation responses to related specific antigens (sonicated T. pallidum), unrelated specific antigens (sheep erythrocytes), and the T cell mitogen, concanavalin A. Results were compared with responses in preinfection sera and in sera from sham-infected rabbits. Titration experiments in which normal serum was used indicated that optimal lymphocyte responsiveness is obtained with a final serum concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For example, as demonstrated by a recent meta-analysis 29 , it is particularly important to state whether or not sample extraction has been conducted before analysis as this greatly affects measurements. There are several different ways to measure OT and its immunoreactive metabolites in peripheral substrates, including enzyme immunoassays (EIA 9 ), radio immunoassays (RIA 30 ), and mass spectrometry applications (i.e., LC–MS 31 , 32 ; nanoLC-MS 33 ). The current paper will focus on EIAs as they appear to be most commonly used in the behavioural sciences and psychology, yet to date only a few published studies conducted and reported validations for OT EIAs using peripheral substrates (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as demonstrated by a recent meta-analysis 29 , it is particularly important to state whether or not sample extraction has been conducted before analysis as this greatly affects measurements. There are several different ways to measure OT and its immunoreactive metabolites in peripheral substrates, including enzyme immunoassays (EIA 9 ), radio immunoassays (RIA 30 ), and mass spectrometry applications (i.e., LC–MS 31 , 32 ; nanoLC-MS 33 ). The current paper will focus on EIAs as they appear to be most commonly used in the behavioural sciences and psychology, yet to date only a few published studies conducted and reported validations for OT EIAs using peripheral substrates (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%